Exploring demographic influences on L2 learners' comprehension of conversational implicatures - Çiftlikli Hapci, Safiye (Frontiers in Language Sciences, 2025)
Maintaining effective communication is more than articulating words—it is pivotal to understanding beyond what is explicitly said. While pragmatic competence is widely recognized as a fundamental aspect of language learning and also communicative competence, limited research has been conducted to determine whether L2 learners' ability to comprehend conversational implicatures varies based on demographic factors. In this case, this study is grounded to examine whether EFL learners' comprehension of conversational implicatures differs with respect to gender, culture of origin, and academic majors. The study employed a quantitative research design and was conducted with 122 first-year university students from various academic majors at a private university in Northern Cyprus. Data were collected via a Multiple-Choice Discourse Completion Test (MCDCT), and the collected numerical data were analyzed via T-Test. The findings reveal notable differences in participants' comprehension of conversational implicatures based on culture of origin and academic majors. Specifically, students from Iran and Nigeria performed higher than those from other cultural groups, while students from the Faculty of Law achieved the highest mean score compared to other majors. By contrast, no significant difference was found between male and female learners. These results emphasize the need for developing L2 learners' comprehension of conversational implicatures in foreign language education by considering learners' demographic factors. Future studies should focus on effective instructional strategies tailored to diverse learner backgrounds to foster comprehension of conversational implicatures and maintain effective communication.